Copper induced synthesis of graphene using amorphous carbon. (June 2016) - Narula, Udit; Tan, Cher Ming; Lai, Chao Sung
Abstract: Copper is approaching its reliability limits with respect to electromigration due to very high current density as a result of continuous technology scaling. Graphene on the other hand has excellent electrical and thermal properties which can prove to be a vital candidate for improving the reliability performance of copper interconnections in ULSI. Possibility of crystallization of amorphous carbon into graphene catalyzed by copper thin film is demonstrated in this work, as evidenced by the Raman, XPS and SIMS analysis, and the number of graphene layer synthesized can be modified with the method developed. As the synthesized graphene layers are on top of the copper film whilst the amorphous carbon source is below the copper film, no contamination of the graphene layer is presence with the method developed, improving the quality and uniformity of the grown graphene layers. Highlights: Graphene is synthesized successfully from a-C beneath a sputtered Cu thin film. Raman, SIMS and XPS characterization shows evidence of the presence of graphene on Cu. Synthesized graphene is not contaminated as a-C layer is not in direct contact with it. Variation in thickness of a-C layer results in different numbers of graphene layers.